Distribution of Chlorophyll-α Contents in the Surface Water along the Course of the FUJI to and from Antarctica in 1972-1973 - Kazunori KURODA (National Institute of Polar Research, 1978)
Measurements of chlorophyll-α and phaeophytin at the surface were carried out by fluorometric methods on board the FUJI from November 1972 to April 1973. The chlorophyll-α contents were relatively high in the coastal region of Japan, the Makassar Strait, the Subantarctic region, the area from 82° to 104°E south of the Antarctic Convergence, the area from 63° to 67°S on the meridian of 15°E, the area off the southern coast of Africa and the Malacca Strait. The distributional patterns of chlorophyll-α obtained by the present investigation were generally similar to those of the previous investigations. The mean values of chlorophyll-α and percentages of chlorophyll-α to the sum of chlorophyll-α and phaeophytin were extremely low in the Indian Ocean, the western North Pacific Ocean, and the South China Sea. On the other hand, in the Subantarctic and the Antarctic regions, they were high, and in the Malacca Strait, the Celebes Sea and the Makassar Strait the concentrations of chlorophyll-α were almost equal to those in the Subantarctic and the Antarctic regions.